Taiwan and the "China impact" : challenges and opportunities - Schubert, Gunter, editor (New York : Routledge, 2016)
Includes bibliographical references and index
Keywords: China -- Relations -- Taiwan; Taiwan -- Politics and government -- 2000-.; Taiwan -- Relations -- China